Multilevel modeling of technology use, student engagement, and fitness outcomes in physical education classes - Cui, Zhaohang; Song, Yifan; Du, Xiaojuan (Frontiers in Psychology, 2024)
Introduction The integration of technology in educational settings, particularly in physical education, has shown potential in enhancing learning experiences and improving physical health outcomes. This study aims to investigate the effects of technology use on student engagement and fitness outcomes, considering the mediating role of student engagement and the moderating influence of personal attributes. Methods Utilizing a time-lagged design, the research collected data from 513 Chinese undergraduate students (52% male and, 48% female) aged between 18 and 24 years over three waves using structured questionnaires rated on a 5-point Likert scale. Results Results revealed a significant positive relationship between technology use and both student engagement (β = 0.68, p < 0.01) and fitness outcomes (β = 0.60, p < 0.01). Student engagement significantly mediated the relationship between technology use and fitness outcomes (β = 0.57, p < 0.01). Personal attributes moderated the effects of technology use on student engagement (β = 0.54, p < 0.01) and fitness outcomes (β = 0.52, p < 0.01), indicating varied benefits among students based on individual characteristics. Discussion These findings highlight the importance of tailoring technological applications in physical education to individual needs, suggesting that personalized approaches can significantly enhance the effectiveness of technology in improving fitness and engagement.